Safety, tolerability, pharmacokinetics, pharmacodynamics, and efficacy of WBP216, a novel IL-6 monoclonal antibody, in patients with rheumatoid arthritis: A phase Ia randomized placebo-controlled study - Leng, Xiaomei; Tang, Xiange; Hu, Pei; Guan, Xiaoduo; Li, Qian; Huang, Cipo; Zhang, Qiang; Chen, Rui; Zeng, Xiaofeng (Frontiers in Immunology, 2023)
Background: WBP216 is a novel human immunoglobulin G1 (IgG1) monoclonal antibody for interleukin (IL)-6. We aimed to assess the safety, tolerability, pharmacokinetics (PK), and pharmacodynamics (PD) of a single ascending dose (SAD) of WBP216 in patients with rheumatoid arthritis (RA). Methods: In this double-blind, placebo-controlled, SAD, phase Ia study, patients with RA were randomized in a 3:1 (Group A1, 10 mg) and 6:2 (Group A2, 30 mg; Group A3, 75 mg; Group A4, 150 mg; Group A5, 300 mg) ratios to receive either ascending doses of WBP216 or placebo subcutaneously. The primary endpoint was the incidence of adverse events (AEs), while the secondary endpoints were characterization of PK, PD, and immunogenicity of WBP216 and the exploratory endpoints included improvements in RA clinical metrics. All statistical analyses were performed using SAS® version 9.2. Results: A total of 41 subjects (34 females and 7 males) were enrolled in the study. WBP216 was well tolerated in all doses (10-300 mg). Most treatment-emergent AEs (TEAEs; 97.6%) were of grade 1 severity and resolved without any treatment. No subjects experienced TEAEs leading to withdrawal or death during the study. An increase in serum concentration and total IL-6 from baseline was observed, while a substantial decrease in high-sensitivity C-reactive protein (hs-CRP) and erythrocyte sedimentation rate (ESR) was observed in all the WBP216 groups. Anti-drug antibodies were detected in only one subject after dosing, indicating an acceptable immunogenicity profile. Limited ACR20 and ACR50 response was observed in the WBP216 groups and no response in the placebo group. Conclusion: WBP216 demonstrated a good safety profile and evidence of potential efficacy in the treatment of patients with RA.